'n Stap in die rigting van 'n oorkoepelende kern-teorie vir kommunikasie - Linda Venter (Communicare)
System theory is the most general theoretical approach to communication and the Pragmatic/system approach can be seen as the most comprehensive communication theory at present. However, It does not address in transpersonal or transpersonali/vertical/religlous communication. According to this approach, the smallest unit in a system is soon as the communication relationship between two individuals. This results in a fundamental inconsistency with the General System Theory, according to which the smallest unit of a system determines the functioning and effectivity of the total system. In this article it is proposed that the smallest unit of the communication system is intrapersonal communication (and sometimes transpersonal communication), which will determine and constrain interpersonal communication. Those levels of communication are not taken into account because they cannot be measured in an empirical way. This caveat is ad dressed by developing a hierarchical communication model which embraces both aforementioned levels of communication, as well as the ultimate supra system, namely the transcendental reality. The nature of the transcendental reality is non-empirical and the transpersonal communication subsystem functions as a bridge between the empirical reality and the transcendental (non-empirical) reality. This model places communication within the domain of a more holistic world view and opens the field to non-linear research that goes beyond the empirical perspective.